2012
DOI: 10.12659/msm.883270
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniae in adult community-acquired pneumonia increases matrix metalloproteinase-9 serum level and induces its gene expression in peripheral blood mononuclear cells

Abstract: SummaryBackgroundThe objective of this study was to assess the concentration of metalloproteinase-2 (MMP-2) and metalloproteinase-9 (MMP-9) in peripheral circulation and their mRNA expression in peripheral blood mononuclear cells (PBMCs) in patients with CAP caused by M. pneumoniae.Material/MethodsWe prospectively analyzed MMPs in 40 hospitalized patients with M. pneumoniae CAP on admission, and in the convalescent phase. Twenty healthy men were used as controls. Quantitative real-time PCR and ELISA tests were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…We performed a zymographic analysis to determine active and inactive MMPs in the serums of CAP patients and controls. Active forms of MMP-2 and MMP-9 were 13 and 17 times higher, respectively, in CAP patients than controls, making our findings consistent with the results of previous studies (6,23,24,(26)(27)(28).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We performed a zymographic analysis to determine active and inactive MMPs in the serums of CAP patients and controls. Active forms of MMP-2 and MMP-9 were 13 and 17 times higher, respectively, in CAP patients than controls, making our findings consistent with the results of previous studies (6,23,24,(26)(27)(28).…”
Section: Discussionsupporting
confidence: 92%
“…However, only a few studies in the literature have investigated the role of MMPs in pneumonia pathogenesis (6,(22)(23)(24)(26)(27)(28). These have shown that patients with hospital-acquired pneumonia (HAP) have excessive MMP-8 and -9 concentrations in plasma and mini-BAL fluids compared to healthy controls (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have examined a possible relationship between MMP-9 and COPD. Plasma levels of MMP-9 have been reported to be increased in α 1 -antitrypsin deficiency-associated emphysema and in COPD, and to correlate negatively with FEV 1 (109,110). Increased plasma levels of MMP-9 have been shown to negatively correlate with FEV 1 and indicate a decline in pulmonary function (111).…”
Section: Common Markers Of Copd and Pneumoniamentioning
confidence: 99%